Case Report: Pediatric Chronic Active Epstein-Barr Virus Infection With Giant Sinus of Valsalva Aneurysms and Aorta and Its Branch Dilations - Li, Qirui; Li, Guyu; Shao, Daming; Yarrabolu, Tharak; Yue, Yuan (Frontiers in Pediatrics, 2022)
In pediatric patients with chronic active Epstein–Barr virus infection, cardiovascular damage is one of the rare but serious complications associated with a poor prognosis. Few published articles have demonstrated systemic arterial lesions involving branches of the aorta as cardiovascular complications. Herein, we report a rare pediatric case of CAEBV associated with giant sinus of Valsalva aneurysms and aorta and its branches dilations. Patient died at home 15 months after the onset of the disease. Most patients will die from rupture of aneurysm or acute respiratory failure in a year. Thus, an adequate history and diagnostic work-up with appropriate EBV serological and genome tests following with imaging examinations (echocardiogram or whole-body CT angiogram) is necessary.